Patient preferences and choices as a reflection of trust-A cluster analysis comparing postsurgical perceptions in a private and a public hospital - Royi Barnea; Aviad Tur‐Sinai; Osnat Levtzion‐Korach; Yossi Weiss; Orna Tal (Wiley, 2022)
Abstract Background Active participation of patients in managing their medical treatment is a major component of the patient empowerment process and may contribute to better clinical outcomes. Patient perceptions and preferences affect the patient-physician encounter in a variety of dimensions, such as patient autonomy, freedom of choice and trust in the healthcare system. The Israeli healthcare system is mostly publicly funded, with additional private healthcare services for surgery and other medical treatments. The aim of this study was to compare the perceptions and preferences of patients in the public and private hospitals in Israel. Methods A cross‐sectional study among 545 individuals who had surgical procedures at two hospitals in Israel (one public and one private). A structured questionnaire comprising 23 items was used to collect perceptions via personal telephone interviews. The responses were categorized into five clusters and compared by type of health services provider (public vs. private) and sociodemographic characteristics (gender, age and education level). Results A hierarchical cluster analysis methodology identified five conceptual groups: trust, concern towards medical errors, dialogue between medical staff and the patient/patient's family, confidentiality and staff bias towards more informed patients, or those with supportive families. Four main themes that highlight patients' preferences were found: physical conditions, personal empowerment and perceived autonomy, patient experience and patient-provider encounter communication. Significant differences between the private and the public healthcare systems were found in four clusters: trust and patient care, patient's concerns, the extent of explanation and medical staff's commitment. Differences secondary to sociodemographic parameters were noticed: patients treated at the private hospital scored significantly higher items of trust, medical staff caring and the importance of choosing their treating surgeon, while patients treated at the public hospital scored higher staff commitment to the patient than those treated at the private hospital. Conclusions The study revealed the perceptions underlying the decisions of patients to undergo surgical procedures in public or private hospitals. Mutual learning could pave the way to better patient-physician encounters. Patient or Public Contribution Patients from the two hospitals were involved in this study by responding to the questionnaire. The data presented is based on the patient's responses.